Refinements to the Probabilistic Approach to Fiscal Sustainability Analysis - Frank, Nathaniel (World Bank, Washington, DC, 2012)
This paper relaxes some key assumptions in the probabilistic approach to fiscal sustainability. First, the authors identify structural breaks over the sample period used to estimate the covariance matrix of the shocks to the debt ratios. Second, the assumption of normality of the shocks is dropped by modeling their respective empirical distribution directly, which makes it possible to quantify asymetries and thick tails. Third, the use of fiscal reaction functions is avoided by focusing attention on debt-stabilizing balances.